Does knowledge of physical activity recommendations increase physical activity among Chinese college students? Empirical investigations based on the transtheoretical model - Kahar Abula; Peter Gröpel; Kai Chen; Jürgen Beckmann (Elsevier, 2018)
Background: Based on the transtheoretical model, the current study investigated whether awareness of physical activity (PA) recommendations had an impact on the stages of PA behavior change and levels of PA among Chinese college students. Methods: In Study 1, with a cross-sectional study design, 9826 students were recruited, and their knowledge of international PA recommendations, PA stage distribution, and self-reported PA level were surveyed. Pearson's χ2 test was used to test whether those participants who were aware and not aware of PA guidelines were equally distributed across the stages of PA behavior, and independent t test was conducted to test the group difference in the actual levels of PA. In Study 2, 279 students who were not aware of the PA recommendations were randomly allocated to either an intervention group or a control group, and only those in the intervention group were presented with international PA guidelines. In both groups, students' PA stages and PA level were examined before the test and then 4 months post-test. McNemar's test for correlated proportions and repeated-measures analysis of variance were conducted to examine the changes in PA stage membership and PA level after the intervention. Results: Study 1 results revealed that only 4.4% of the surveyed students had correct knowledge of PA recommendations. Those who were aware of the recommendations were in later stages of PA behavior (χ2(4) = 167.19, p < 0.001). They were also significantly more physically active than those who were not aware of the recommendations (t(443.71) = 9.00, p < 0.001, Cohen's d = 0.53). Study 2 results demonstrated that the intervention group participants who were at the precontemplation and contemplation stages at the pre-test each progressed further in the PA stages in the post-test (χ2(1) = 112.06, p < 0.001; χ2(1) = 118.76, p = 0.03, respectively), although no significant change in PA level was observed (t(139) < 1, p = 0.89). Conclusion: The results showed that awareness of the PA recommendations was associated with higher stages and levels of PA behavior, and a brief educational exposure to PA recommendations led to improved stages of PA behavior but no change in the levels of PA among Chinese college students. More effective public health campaign strategies are needed to promote the dissemination of the PA recommendations and to raise the awareness of the Chinese student population.